(untitled) (Journal of International Crisis and Risk Communication Research, 2022)
In our previous editorials, we have touched on different aspects of diversity and diversification in crisis and risk communicationresearch. We have argued that while the field is starting to expand from its focus on Western corporate perspectives to includenon-Western countries, non-corporate crises, and more broadly embracing different perspectives, we also suggest that diversificationneeds to continue to develop and be supported (Diers-Lawson & Meißner, 2021a). Furthermore, we have reviewed the multidisciplinary character of crisis and risk communication research, involving researchers from fields like public relations, political science, sociology, journalism, public health, and others suggesting this is not only healthy for the continued development of crisis and risk communication research but also necessary to more fully understand the phenomenon (Diers-Lawson & Meißner, 2021b).